(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study examined the influence of Artificial Intelligence on Delivery of Business Education courses in Universities in South-East. Two research questions were answered and two hypotheses tested at 0.05 level of significant. The research design was a descriptive survey. The population of the study was 80 Business Educators from Federal and State Universities in South-East. The instrument for data collection was a self-structured questionnaire and was validated by three experts while the reliability of the instrument was ascertained using Cronbach Alpha reliability method which yielded a reliability co-efficient of 0.78. Data collected were analyzed using mean and standard deviation to answer the research question while t-test was used to test the hypotheses. The results indicated that AI can influence instructional delivery of Business Education courses to a very high extent positively. It also revealed that it can influence instructional delivery of Business Education courses to a high extent negatively. There was no significant difference in the meaning rating of Federal and State Business Educators on the positive and negative influence of AL on instructional delivery of Business Education courses in Universities in South-East. The study recommended among others that awareness of AI should be enforced in all the universities in South-East to update the lecturers on the need for implementation of AI and its application in the teaching and learning processes.